The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.4155/bio-2021-0071
|View full text |Cite
|
Sign up to set email alerts
|

A Flow Cytometric Journey Into Cell Cycle Analysis

Abstract: Cell cycle involves a series of changes that lead to cell growth and division. Cell cycle analysis is crucial to understand cellular responses to changing environmental conditions. Since its inception, flow cytometry has been particularly useful for cell cycle analysis at single cell level due to its speed and precision. Previously, flow cytometric cell cycle analysis relied solely on the measurement of cellular DNA content. Later, methods were developed for multiparametric analysis. This review explains the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 164 publications
0
9
0
Order By: Relevance
“…Events (10.000) were evaluated by flow cytometry (BD FACSverseTM). All data were analyzed using FlowJo Software v.10 [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…Events (10.000) were evaluated by flow cytometry (BD FACSverseTM). All data were analyzed using FlowJo Software v.10 [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cell cycle analysis plays a crucial role in understanding the cellular state and changes in different environments. [ 53 ] The cell cycle distribution was investigated using unmodified cells as a reference. The results showed that the effects of cell surface engineering reactions on HUVECs and HSFs were significantly different (Figure S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The cells were resuspended in 100 μL of 1X PBS, and 5 μL (5 mg/mL) of propidium iodide (PI) was added, and samples were incubated for 30 min at room temperature. The samples were run in a flow cytometer by using BD LSRFortessa TM Cell Analyzer, and data were analyzed using FACS analysis software (FlowJo TM v 10.8 BD bioscience, San Jose, CA, USA) [ 66 ].…”
Section: Methodsmentioning
confidence: 99%